PERCEPTIONS OF INDUSTRIAL DESIGN TEACHERS ON DESIGN THINKING IN MALAYSIAN ART SCHOOLS - Mohd Mokhtar Muhammad; Mohamad ‘Adillas Ahmad Fesol; Siti Feirusz Ahmad Fesol (Journal of Islamic, Social, Economics and Development, 2024)
Education in Malaysia is taking a significant step towards embracing the wave of Industrial Revolution 4.0 to align with the demands of current progress. With this progress, creativity has become a vital asset in generating new ideas, which are crucial in various aspects of thinking. The education system required in the era of IR 4.0 must not only produce lifelong learners but also individuals with a comprehensive set of skills that adapt to today's rapid changes. In this context, creativity plays a central role in the process of design thinking (DT), which is essential for meeting current and future market demands. DT is a relatively new approach and has been integrated into the Industrial Design curriculum at Sekolah Seni Malaysia (SSeM) as part of the National Secondary School Curriculum (KSSM) since 2019. Given this intriguing integration, the main objective of this study is to explore and deepen our understanding of teachers' perceptions of implementing design thinking in teaching and learning for Form 4 students in the Industrial Design subjects at selected SSeM. This study employs a case study-based qualitative research methodology, with teachers who experienced in teaching Industrial Design as the subject matter expert. The results were analysed using an axial coding process, leading to sub-theme categorization. The findings reveal that DT, encompassing the entire design process, provides distinct advantages for both students and teachers by expanding their knowledge from familiar to unfamiliar contexts. This implementation empowers students to develop their design-based metacognitive strategies for solving novel problems.